2016
DOI: 10.1146/annurev-bioeng-111215-024421
|View full text |Cite
|
Sign up to set email alerts
|

Design of Catalytic Peptides and Proteins Through Rational and Combinatorial Approaches

Abstract: This review focuses on recent progress in noncomputational methods to introduce catalytic function into proteins, peptides, and peptide assemblies. We discuss various approaches to creating catalytic activity and classification of noncomputational methods into rational and combinatorial classes. The section on rational design covers recent progress in the development of short peptides and oligomeric peptide assemblies for various natural and unnatural reactions. The section on combinatorial design describes re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 108 publications
0
42
0
Order By: Relevance
“…When the development of such natural bioactive metabolites falls short for the generation of new antimicrobial agents, other approaches should be applied, such as rational design. In general, rational designs use existing knowledge regarding a molecule's structure or a reaction of interest, combining computational tools and structural knowledge [155]. There are two main chemoinformatics approaches for obtaining new fungicides or other bioactive compounds: structure-based and ligand-based drug design [156].…”
Section: Chemoinformatics Approaches For Obtaining New Fungicidesmentioning
confidence: 99%
“…When the development of such natural bioactive metabolites falls short for the generation of new antimicrobial agents, other approaches should be applied, such as rational design. In general, rational designs use existing knowledge regarding a molecule's structure or a reaction of interest, combining computational tools and structural knowledge [155]. There are two main chemoinformatics approaches for obtaining new fungicides or other bioactive compounds: structure-based and ligand-based drug design [156].…”
Section: Chemoinformatics Approaches For Obtaining New Fungicidesmentioning
confidence: 99%
“…Thus it is hardly surprising that only a handful of successful protein/peptide designs capable of promoting redox reactions have been reported so far. [4] …”
mentioning
confidence: 99%
“…Whereas various biological molecules, including pigments, nucleic acids and proteins are utilized for nanoparticle synthesis and functionalization [7][8][9][10][11][12][13], peptides also comprise promising ligand molecules 2 of 10 that bind, not only metallic ions, but also metallic crystals. This is because variants are designed abundantly from combinations using amino acids with various physicochemical properties through chemical synthesis [14][15][16][17][18]. Among a wide range of functional peptides, catalytic peptides used for nanoparticle synthesis regulation, named mineralization peptides, have commonly been isolated from peptides that are strongly bound to target crystals [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…This is because variants are designed abundantly from combinations using amino acids with various physicochemical properties through chemical synthesis [14][15][16][17][18]. Among a wide range of functional peptides, catalytic peptides used for nanoparticle synthesis regulation, named mineralization peptides, have commonly been isolated from peptides that are strongly bound to target crystals [14][15][16]. Considering the chemical equilibrium of crystalline nanoparticles and their metallic ions in solution, it has been suggested that the strong binding of peptides stabilizes the crystals, resulting in a shift in the equilibrium from an ionic state towards that of the crystal; specifically, target crystal mineralization is mediated by peptide addition.…”
Section: Introductionmentioning
confidence: 99%